Educational Work In Higher Educational Institutions as an Important Social-Educational Factor - Negkadamovich, Rakhmatov (Buletin Antropologi Indonesia, 2025)
in this article, the author considers the system of continuous education, the main principles of state policy at all its stages. He recognizes the opportunities for the full realization of the talents and abilities, noble aspirations of our youth In the new Uzbekistan, pays attention to the issues of studying and scientific analysis of the spiritual heritage, its reflection and harmonization in the educational process of our youth, and gives his practical recommendations for the educational work of students of higher educational institutions.